1992
DOI: 10.1007/bf00029151
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana small subunit leader and transit peptide enhance the expression ofBacillus thuringiensis proteins in transgenic plants

Abstract: The expression of the modified gene for a truncated form of the cryIA(c) gene, encoding the insecticidal portion of the lepidopteran-active CryIA(c) protein from Bacillus thuringiensis var. kurstaki (B.t.k.) HD73, under control of the Arabidopsis thaliana ribulose-1,5-bisphosphate carboxylase (Rubisco) small subunit ats1A promoter with and without its associated transit peptide was analyzed in transgenic tobacco plants. Examination of leaf tissue revealed that the ats1A promoter with its transit peptide sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 25 publications
1
40
1
Order By: Relevance
“…Specificity of Construct-Specific Methods for NL, NLP and NLY In NL, the e-p-35Ssequence 17) is used to regulate the expression of the cryIIIA gene, whereas the riblose-1,5-bisphosphate carboxylase small subunit ats1A promoter (PArab-SSU1A) 18) is used to control the cryIIIA gene expression in NLP and NLY. Therefore, the construct-specific primer pair, NL 01-5Ј/NL 01-3Ј, was designed in the junction between e-p-35S and cryIIIA to specifically detect NL.…”
Section: Specificity Of Screening Methods For the Detection Of Gm Potamentioning
confidence: 99%
“…Specificity of Construct-Specific Methods for NL, NLP and NLY In NL, the e-p-35Ssequence 17) is used to regulate the expression of the cryIIIA gene, whereas the riblose-1,5-bisphosphate carboxylase small subunit ats1A promoter (PArab-SSU1A) 18) is used to control the cryIIIA gene expression in NLP and NLY. Therefore, the construct-specific primer pair, NL 01-5Ј/NL 01-3Ј, was designed in the junction between e-p-35S and cryIIIA to specifically detect NL.…”
Section: Specificity Of Screening Methods For the Detection Of Gm Potamentioning
confidence: 99%
“…In the accompanying paper (Diehn et al, 1998) One approach used in the design of synthetic B.t.-toxin genes has been to modify A/T-rich sequences resembling known sequences involved in RNA processing or stability by converting codons in the target sequences to synonymous codons typically used in plant genes (Perlak et al, 1990(Perlak et al, , 1991(Perlak et al, , 1993Sutton et al, 1992;van der Salm et al, 1994). It has been suggested that the abundance of rare codons in B.t.-toxin genes could cause inefficient translation, resulting in poor expression in plants (Vaeck et al, 1987;Murray et al, 1991;Perlak et al, 1991;Wong et al, 1992), although this remains unproven. Based on this latter hypothesis, however, other synthetic B.t.-toxin genes giving high expression in plants have been constructed that primarily incorporate sequence modifications intended to convert rare codons to plant-preferred codons (Adang et al, 1993;Fujimoto et al, 1993;Koziel et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…HD73, under control of the Arabidopsis thaliana ribulose-l,5-bisphosphate carboxylase (RuBisCO) small subunit atsiA promoter with and without its associated transit peptide was analysed in transgenic tobacco plants. The examination of leaf tissue revealed that the atslA promoter with its transit peptide sequence fused to the truncated cryiA(c) protein provided a 10-fold to 20-fold increase in cryiA(c) mRNA and protein levels compared to gene constructs in which the cauliflower mosaic virus 35S promoter with a duplication of the enhancer region (CaMV-En35S) was used to express the same cryiA(c) gene (Wong et al 1992). Fujimoto et al (1993) Gittins et al (2000) studied the ability of heterologous RuBisCO small-subunit gene promoters, Rbss3CP (0.8 kbp) from tomato (Lycopersicon esculentum Mill.)…”
Section: Rubisco Small Subunit Promoter As a Green Tissue-specific Prmentioning
confidence: 99%